Prevalence of sexual dysfunction and associated factors among essential hypertensive women attending hypertensive and out-patient clinics HUSM - Latif, Rozimah Abdul (2011)
Objective To determine the prevalence of sexual dysfunction and associated risk factors in hypertensive women. Research Design and Methods Data was collected from 348 hypertensive women in the Hypertensive and Out Patient Clinic of Hospital Universiti Sains Malaysia using Malay Version of Female Sexual Function Index. Socio-demographics, marital profiles, obstetric and gynaecological problems, presence of hypertension, presence of other medical illness and husband chronic illness were recorded. Results The prevalence of sexual dysfunction among hypertensive women was 21.3% (95% CI: 17.00, 25.60). Desire disorder was reported as the highest percentage (42.8%), followed by lubrication disorder (24.1%), arousal disorder (22.7%), satisfaction and sexual pain disorder (19.0%) and orgasm disorder (14.1%). Less frequent sexual intercourse, lack of satisfaction with husband's sexual performance, unhappy marriage, having urinary incontinence and ACE I administration were significant associated factors for sexual dysfunction in hypertensive women. Conclusion The result showed that almost 1 in 5 hypertensive women suffered from sexual dysfunction. This indicates that sexual dysfunction is a major public health concern and health care providers should be more serious in evaluating this issue.